Evaluating the Performance of a Rural, Field-Based Teacher Training Program - John M. Booker; Richard E. Riedl (Journal of Research in Rural Education, 1987)
Course completion rates as a routine measurement of performance in higher education are generally accepted, at least implicitly, as a feature of institutional life. When these institutional standards are applied to an innovative, rural field-based teacher training program, the resulting conflict over the evaluation of performance brings a re-consideration of such conventional practices. This study finds that the most successful field-based students, the graduates, show the worst performance when some conventional standards for course completions are applied. Some implications of these findings for innovation and change in higher education are reviewed.